Fabrication, fouling and foulant analyses of asymmetric polysulfone (PSF) ultrafiltration membrane fouled with natural organic matter (NOM) source waters - Zularisam, A. W.; Ismail, Ahmad Fauzi; Salim, M. R.; A. M., Mimi Sakinah; Hiroaki, Ozaki (Elsevier B.V., 2007)
The fouling behaviours and membrane autopsy protocol for polysulfone (PSF) ultrafiltration membrane fouled with natural organic matter source waters were studied. Samples from Ulu Pontian river which has a relatively hydrophilic NOM source water and Bekok Dam river which has a relatively hydrophobic NOM source water have been used as the case study. Fouling characteristics of the NOM source waters were assessed by filtering the feed water with an immersed hydrophobic PSF ultrafiltration membrane. The asymmetric hollow fiber PSF membrane was spun by a dry–wet phase inversion spinning process. The membrane autopsy protocol was performed to identify the nature of the deposited foulants and their relative effects on membrane characteristics. Results for the relatively hydrophilic NOM source water (Ulu Pontian river) exhibited greater flux decline but lesser NOM removal considerably due to pore adsorption, indicating that the low molecular weight, aliphatic linear structure and neutral/base organic matter contained within the hydrophilic fraction were the prime foulants. In contrast, relatively hydrophobic NOM source water (Bekok Dam water) that possessed higher charge density, greater molecular weight and bulky aromatic structure has exhibited lesser flux decline and better NOM rejection noticeably due to cake deposition, despite filtering through a hydrophobic membrane, thus suggesting that the electrostatic repulsion was more influential than the steric hindrance mechanisms. In comparison a non-charged model compound (polyethylene glycol) of similar molecular weight was used to quantify the role of electrostatic charge repulsion on NOM rejection. Moreover, analyses on the permeate characteristics revealed that the hydrophobicNOMwas preferentially removed by the negatively charged PSF membrane as opposed to the hydrophilic NOM, hence, suggesting that the charge interactions, in addition to size exclusion were more crucial to NOM removal. The membrane autopsies analyses confirmed the flux decline results and permeate analyses as the filtered-membrane was mainly fouled by the hydrophilic NOM components rather than humic compounds. Distinctive changes were observed in membrane characteristics in terms of ionizable functional groups, membrane wettability and zeta potential. ATR-FTIR analysis revealed that hydrophilic components such as the polysaccharides-like substances, alcoholic compounds and aliphatic amide of protein groups as the responsible materials covering the membrane surface. Morphological analyses using SEM indicated different fouling mechanisms occur for both NOM sources associated with differences in the relative NOM constituent distributions, NOM structural variations and NOM removal mechanisms